Enhancing Operational Performance Index Using the Theory of Constraints: A Case Study at PT XYZ - Savitri, Gusti Ayu Made Hanny Dian (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2025)
Since the onset of the COVID-19 pandemic, car sales in Indonesia have declined, affecting PT XYZ, a subsidiary of a major automotive company specializing in pre-owned vehicle sales. This study aims to develop a strategy for identifying profitable and fast-selling car types using the Theory of Constraints approach. This applied research employs a mixed-method, including both qualitative and quantitative methods. The qualitative approach involves interviews with three key informants, while the quantitative method uses the Theory of Constraints to assess operational performance through inventory turnover and productivity. A Chi-Square test is also conducted to examine the relationship between these two factors. The study's findings indicate a relationship between inventory turnover and productivity. This suggests that changes in one factor can impact the other, influencing PT XYZ's operational strategies to enhance efficiency and profitability in used car sales. Therefore, the company should consider this relationship when making decisions, including vehicle purchasing and refurbishment planning, to optimize sales performance.